EFEITO DA SUPLEMENTAÇÃO COM SULFATO FERROSO SOBRE STREPTOCOCCUS MUTANS: UM ESTUDO CLÍNICO. - PROENÇA, Mariana Almeida Mello (2013)
An anti-mutans effect of ferrous sulfate was observed in experimental models in vitro, in animals and in situ, but this effect is unknown when the ferrous sulfate is administered orally as a supplement for the treatment of anemia due to iron deficiency. The aim of this clinical trial was to evaluate the effect of ferrous sulfate on Streptococcus mutans (SM) present in dental plaque and saliva of children with early childhood caries (ECC). The sample consisted of 14 children aged 36 to 71 months diagnosed with iron deficiency anemia (Hb < 11.0 g/dl or serum ferritin < 30 μg/l). Children with debilitating systemic diseases and/or who had undergone treatment for iron deficiency anemia in the last six months prior to sample collection were excluded. The suplementation was carried out with ferrous sulphate (4mg/kg/day) for 60 days. The plaque and saliva samples were collected prior to the start of supplementation with ferrous sulfate (baseline) and 60 days after the start of treatment. Biofilm and salivary samples were collected before treatment start (baseline) and 60 days after. We carried out the quantification of colony forming units (CFU) in samples SM biofilm (CFU/mg) and saliva (CFU/ml) and optical density analysis of IgA anti-mutans. To compare the effects before and after supplementation was used paired t test (BioStat 5.0), with the significance level set at 5% test. Ferrous sulfate supplementation had no effect on count of MS biofilm’s (p = 0.4). In the salivary samples was observed that the reduction in CFU count of SM was at the limit of significance (p = 0.053). However, there was a reduction of IgA antibodies anti-mutans between baseline and 60 days (p = 0.016). The results of this study suggest that supplementation with ferrous sulfate has an effect anti-mutans in saliva of children with ECC.